2021
DOI: 10.1177/08971900211015080
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressor Discontinuation Order in Septic Shock With Reduced Left Ventricular Function

Abstract: Background: The optimal vasopressor management for septic patients with left ventricular (LV) dysfunction has not been well established, and current evidence is conflicting regarding the optimal vasopressor discontinuation order. Objective: The objective was to evaluate the impact of LV dysfunction on the hemodynamic management of septic shock by assessing the incidence of clinically significant hypotension after vasopressor discontinuation. Methods: In this single-center, retrospective cohort study, adult pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In contrast, in an individual patient data metaanalysis, including the sole randomized trial and several observational studies, the cessation or tapering of norepinephrine first was associated with less frequent hypotension without affecting short-term mortality (184). However, other studies reported similar rates of hypotension occurrence (185). It might be attractive to evaluate endogenous release of vasopressin to predict hypotension occurrence after cessation of exogenous vasopressin infusion.…”
Section: B4: For Patients With Septic Shock Receiving Norepinephrine ...mentioning
confidence: 99%
“…In contrast, in an individual patient data metaanalysis, including the sole randomized trial and several observational studies, the cessation or tapering of norepinephrine first was associated with less frequent hypotension without affecting short-term mortality (184). However, other studies reported similar rates of hypotension occurrence (185). It might be attractive to evaluate endogenous release of vasopressin to predict hypotension occurrence after cessation of exogenous vasopressin infusion.…”
Section: B4: For Patients With Septic Shock Receiving Norepinephrine ...mentioning
confidence: 99%